A Similar Old Term المماثلة مصطلح قديم جديد - Samira Abdelmalek سميرة عبد المالك (Journal Of Babylon Center For Humanities Studies, 2018)
The Similarity of the vocal phenomena that help to harmonize the word, and facilitate pronunciation, and similar as a term did not appear in the books of the old, but under other names in the same context, but similar sound phenomenon addressed by the old and separated, and what is calculated for the modern is The regulation of the phenomenon and its classification research becomes easy to understand for learners